Scour Risk Analysis of Existing Bridge Pier Based on Inversion Theory. Issue 1 (2nd January 2018) - Han, Bing; Xie, Hui-Bing; Yan, Wu-Tong; Lei, Da-Chen; Zhu, Li; Wang, Yu-Qian; Li, Huichi
Abstract: Scour around bridge piers might cause a decrease in lateral support at bridge foundations, and the simultaneous lateral loads would threaten the safety of existing bridges across rivers. Mitigation of foundation scour should be performed based on a comprehensive assessment of scour risk, combined with a thorough investigation of the uncertainties associated with the risk assessment procedure. However, in the commonly used risk assessment processes, identification of risk sources and determination of uncertainty propagation are based on experts' experience. Moreover, the measured data from inspection of existing bridges cannot be fully utilized. In this paper, an inversion-theory-based method is proposed to evaluate the probability of risk events. First, risk sources were identified through an analysis of equations specified in Chinese bridge design codes. Based on the proposed method, prior information of the risk factors and measured scour data were taken into account, so that posterior distribution and statistical characteristics of the several risk sources could be obtained. Finally, the probability of risk events was determined and uncertainty propagation between risk sources and risk events revealed. To verify the proposed method and analyze the influence of prior information on the result, a case study was conducted and the information requirements of the method discussed.